Investigating storms - Housel, Debra J. (Earth and space science readers., 2007)
There are many causes for different kinds of weather, but the biggest factors are heat, water, and wind. For example, the reason why one type of precipitation falls instead of another is usually because of the air temperature. Today, there are many scientific instruments that help predict the weather. These instruments help people prepare for storms before they happen.